The Effect of Compensation and Service Period on Employee Performance at PT. Infomedia Nusantara Branch Bandung - Kosasih Kosasih; Nurjaya Nurjaya; Denok Sunarsi (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
This study aims to determine the effect of compensation and tenure on employee performance at PT. Infomedia Nusantara Bandung Branch. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that compensation has a significant effect on employee performance by 50.7%, hypothesis testing is obtained t count > t table or (12.117 > 1.977). The working period significantly affects employee performance by 38.8%; hypothesis testing is obtained t count > t table or (9.513 > 1.977). Compensation and tenure simultaneously have a significant effect on employee performance with the regression equation Y = 9.873 + 0.482X1 + 0.269X2, and the contribution of the effect is 55.4%, hypothesis testing is obtained F count > F table or (88.055 > 2.670).